Complementarity of Image and Text in Political Cartoons: Three Case Studies - Dafina Genova (Anglica. An International Journal of English Studies)
The article analyzes the complementarity of image and text in political cartoons taking into account the following parameters: Prior Text(s), Producer, Cartoon, and Viewer/ Reader. In the meaning-making process, the viewer/reader constantly alternates between image and text. The two modes of communication can convey the same message(s), each of the modes can strengthen the meaning of the other; the two might have nothing in common, yet, when combined, will produce a meaningful message. Visual metaphors and metonymies play an important role in the construction of meaning in political cartoons. They are analyzed from the point of view of conceptual metaphor and metonymy theory and its application in multimodal communication. Humour in political cartoons is also briefly discussed.